TString: a tool to locate the target string’s screen based on automatic exploration - Felipe, Lais; Miranda, Breno; Couto, Maria (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2024)
Developing localized software applications for multiple languages can significantly expand a developer’s potential consumer base, offering strong economic incentives. When targeting the global market, it is essential to adapt content to the specific region, culture, or country that the software will serve. Therefore, Localization (l10n) and Internationalization (i18n) testing are crucial for ensuring a seamless user experience, regardless of the locale settings on the application. A key task in localization testing is validating textual content (strings), which often relies heavily on the tester’s experience to locate screens containing the strings that need validation. However, the limited availability of automated tools for localization and internationalization testing results in labor-intensive, repetitive manual work. This research seeks to address these challenges by (i) introducing TString, a tool designed to assist localization and internationalization testers in identifying screens containing specific strings for validation, and (ii) conducting a preliminary evaluation to assess the usefulness of TString in an industrial context. To assess the tool’s usability, the System Usability Scale (SUS) was employed. A group of localization/internationalization testers received an overview of the tool and subsequently completed the SUS questionnaire. The tool achieved highly positive results, with scores ranging from 92.5 to 100, indicating strong acceptance and a high likelihood of meeting the testers’ needs.